Advanced Material and Device Applications with Germanium - Lee, Sanghyun (IntechOpen, 2018)
Germanium is an elemental semiconductor, which played an important role in the birth of the semiconductor but soon was replaced with silicon. However, germanium is poised to make a remarkable comeback in the semiconductor industry. With this increasing attention, this book describes the fundamental aspects of germanium and its applications. The contributing authors are experts in their field with great in-depth knowledge. The authors strongly feel that this contribution might be of interest to readers and help to expand the scope of their knowledge.